(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Farmers’ intentions to commercialize is hinged on a variety of heterogeneous factors. Entrepreneurial intention is important for any decision to start any farm business. Intention is an unswerving antecedent of actual behaviour, and the more robust intention for behaviour, the greater the success of behaviour prediction. The study adapted the modified entrepreneurial potential model to exemplify factors influencing farmers’ intentions to adopt commercialization. The study employed validated variables, and used in the context of willingness to commercialization of individual farm. The measurement variables were perceived desirability (attitude and social norms), perceived feasibility (self-efficacy) and credibility. The findings extrapolated from the ordinal logistics regression wereperceived desirability (P< 0.050), perceived feasibility (P< 0.045), credibility (P< 0.038), and propensity to act (P<0.000). Furthermore, each of the attitudinal antecedents were significant and positively related to farmers’ intentions to commercialize. Surmounting farm commercialization barriers requires upgrading existing farm infrastructures and upskilling farmers to adapt to farm precision and innovation. The paper recommends, that for subsistence farmers to transition to commercial farming or potential entrepreneurs; the government should identify and adopt policies that will increase farmers’ perceived feasibility and perceived desirability.